Paradigma Baru Bagi Pendidikan Masa Depan Indonesia - Ajeung Laras Nurbaity; Dinie Anggraeni Dewi (Civiliza Publishing, 2021)
The dynamics of education in development involving our policy makers today have weaknesses, both theoretical, methodological and empirical. However, in reality, the technological skills received from formal educational institutions are not in accordance with existing needs. By examining this alternative learning paradigm, educators or prospective educators are expected to be able to see a problem, take actions / decisions related to learning wisely so that efforts to develop the potential of students are the estuary of all learning activities.